Why Escalate?: Symbolic Territory and Strategy Choice in Conflicts Over Self-Determination - Friederike Luise Kelle (Nationalism and Ethnic Politics, 2021)
The quest for self-determination on the basis of shared identities motivates many subnational conflicts worldwide, but our understanding of the linkages between identity, contested land, and strategies is incomplete. What role do symbolic territorial attachments play for strategy choice in self-determination demands? I argue that groups tend to escalate their demands if they can exploit mobilization advantages of symbolic territory, creating identity-based territorial focal points for mobilization. I present new data on strategy choice in self-determination demands worldwide between 2005 and 2015. Using multinomial logit estimations, I find that symbolic territory contributes to limited degrees of escalation, and discourages armed conflict.
Keywords: 300